W pogoni za fantazmatem miłości. Na marginesie opowiadań Zygmunta Haupta - Nęcka, Agnieszka (Tematy i Konteksty, 2011)
The author of the article uses the theories by, among others, Barthes and Bataille in order to analyze complicated male-female relations in the selected writings by Zygmunt Haupt – one of the most interesting and, at the same time, the most underestimated writers of the XXth century. The article discusses eroticism in the prose by the author of Pierścień z papieru as a result of autobiographical character of Haupt’s texts and as one of the main topics of his writings. However, the article does not only dwell on the “traditional” understanding of problems with establishing contacts with another sex or the inability to maintain the so-called appropriate relationships between men and women. The narrator of the short novels by Haupt refers also – in more or less explicit manner – to incestuous relations with Electra/Nietota. Due to this fact the problematization of unfulfilled love – feeling that cannot flourish because of various obstacles (cultural, social and moral rules, as well as simply death of the beloved one) – can be discussed. Such problematization is also the reason for replacement of coherent narration with a set of digressions that are perceived, in the terminology proposed by Barthes, as “fragments of love discourse”. Such replacement results in, among others, idealization of body parts, peculiar play with time or common indulgence in fantasies.